PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN BUDAYA ORGANISASI PADA KINERJA ORGANISASI DENGAN MOTIVASI KERJA SEBAGAI PEMODERASI - Asmara, I Kadek Jati; Widanaputra, Anak Agung Gde Putu (E-Jurnal Akuntansi; Vol 18 No 2 (2017), 2017)
Purpose of this study to determine effect of transformational leadership style on performance LPD, LPD organizational culture on performance, and motivation moderate relationship of transformational leadership style on performance LPD and LPD organizational culture on performance. The study was conducted at LPD in Badung. The sample is determined by probability sampling method with stratified random sampling technique proportiante obtain sample 55 LPD. Data analysis technique is Moderated Regression Analysis. The analysis showed that transformational leadership style no effect on performance of organization, organizational culture no effect on performance of organization, motivation not able moderate influence of transformational leadership on organizational performance. Motivation able  moderate organizational culture on organizational performance.
Keywords: transformational leadership, organizational culture, motivation, performance LPD